NEXT TIME IT MIGHT NOT BE HERE: EXPLORING MOTIVATIONS TO PURCHASE LIMITED EDITION FOOD AND BEVERAGE PRODUCTS - Kose, Sirin Gizem; Ozer Cizer, Ece (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
In competitive environments, food and beverage brands frequently launch limited-edition products to increase market share. Within this context, this study aims to investigate the antecedents of purchasing limited-edition food and beverage products in general. Data were collected via copies of questionnaires from 399 Turkish customers. The population of the study is actual and/or potential buyers of limited-edition food and beverage products. Convenience sampling method was used for data collection and the data were analyzed with structural equation modeling method. The study found positive relationships between perceived scarcity, anticipated regret, attitude, and purchase intention of limited-edition food and beverage products (FABP). Results show that attitude is a partial mediator in the relationship between perceived scarcity-purchase intention as well as anticipated regret-purchase intention. The study also presented the moderating role of desire for unique consumer products in the relationship between attitude and purchase intention for limited-edition FABP. Food and beverage brands should consider perceived scarcity, anticipated regret, attitude, and desire for unique consumer product variables while implementing limited-edition strategies.
Keywords: Limited-edition products; food and beverages; perceived scarcity; anticipated regret; purchase intention; desire for unique consumer products; Business & Economics